Control measures to reduce Neospora caninum abortions in dairy farms: a pilot study in Iran - Gharekhani, Jamal; Yakhchali, Mohammad (Veterinaria Italiana, 2022)
Neospora caninum plays an important role in abortion and economic losses in dairy industry worldwide. The main target of this work was to detect the infection rate of N. caninum in various hosts in dairy farms for identifying the risk factors and applying appropriate control programs to reduce the number of abortions. The study was conducted in dairy farms with high incidence of abortion in Hamedan province, West of Iran. After the primary assessment, we conducted a controlling program for reducing the Neospora‑infection rate and associated abortions. Before implementing the control program, the seropositivity was 24.8% in cows (N=476 distributed in 10 farms) and 8.6% (N=185) in dogs. Abortion occurred in 3.57% of pregnant cows. 94.1% of aborted cows were positive for Neospora‑infection. Based on molecular technique, the infection rate was detected in 7.3% of cats (N=41), in 25% of pigeons (N=19)and in 11.8% of rodents (N=51). After the implementation of neosporosis control programs in the farms, the seropositivity of N. caninum decreased to 8.2% in cows and 2.9% in dogs. After the one‑year follow‑up, no cases of abortions were reported in the farms. This was the first parallel evaluation of Neospora‑infection and controlling programs in Iranian dairy farms. Regular control of rodents, retesting of seronegative animals and farm biosecurity measures are recommended for reducing the abortion incidence. The access of dogs to the herd and to aborted materials should be restricted. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />